Influence of dietary supplementation of modified tall oil, chromium nicotinate, and L-carnitine on pork chop display color stability, warnerbratzler shear, and sensory panel traits - Waylan, A.T.; O'Quinn, P.R.; Woodworth, J.C.; Owen, K.Q.; Unruh, John A.; Goodband, Robert D.; Nelssen, Jim L.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighty crossbred (PIC) gilts were used to determine the influence of feeding modified tall oil (MTO, 0 or .5% of diet), chromium nicotinate (0 or 50 ppb), and L-carnitine (0 or 50 ppm) on display color stability, Warner-Bratzler shear, and sensory panel traits of pork chops. Dietary additions of MTO, chromium nicotinate, and L-camitine to growing and finishing swine diets had minimal effects on quality characteristics and display color stability of pork chops. Therefore, producers probably can take advantage of any production or carcass cutability improvement from these feed supplements without affecting muscle quality of pork chops.
Keywords: Swine; Modified tall oil; Chromium nicotinate; L-carnitine; Pork chop